Analysis of learning design using the canva application in information and communication technology (ICT) training - Hasnawati (Balai Diklat Keagamaan Ambon, 2023)
Canva is one of the programs in designing online learning that provides various tools such as presentations, infographic videos. The use of platforms for learning design is an innovation that must be developed by teachers. With the learning design, learning will be active and more interesting. The research used the Research and Development (R&D) method with the ADDIE model. 5 stages in the ADDIE model, namely the stages of analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). The results of the analysis show that the learning design using the Canva application in ICT training for madrasa teachers in Central Maluku district stated that 20% often used the Canva application in designing lessons and 60% had used the Canva platform or application in designing learning, 20% stated that they had never used Canva in designing learning and using the Canva-based learning animation video application.